2017
DOI: 10.1080/15592294.2016.1265711
|View full text |Cite
|
Sign up to set email alerts
|

GPX3 promoter methylation predicts platinum sensitivity in colorectal cancer

Abstract: Epigenetic control of gene expression is a major determinant of tumor phenotype and has been found to influence sensitivity to individual chemotherapeutic agents. Glutathione peroxidase 3 (GPX3, plasma glutathione peroxidase) is a key component of cellular antioxidant regulation and its gene has been reported to be methylated in specific tumor types. GPX3 role in oxidative damage has been associated with sensitivity to platinums in other tumors but its importance in colorectal cancer (CRC) has not been determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 34 publications
0
48
0
2
Order By: Relevance
“…DNA methylation and tissue-specific gene expression are the most common epigenetic alterations. DNA methylation has been used as biomarkers for early diagnosis, progression, and prognosis of various cancers (22)(23)(24). Our results showed that the expression of GPX3 was significantly down-regulated in KBD patients compared with healthy controls, indicating that DNA methylation might suppresses the expression of GPX3.…”
Section: Accepted Manuscript 13mentioning
confidence: 65%
“…DNA methylation and tissue-specific gene expression are the most common epigenetic alterations. DNA methylation has been used as biomarkers for early diagnosis, progression, and prognosis of various cancers (22)(23)(24). Our results showed that the expression of GPX3 was significantly down-regulated in KBD patients compared with healthy controls, indicating that DNA methylation might suppresses the expression of GPX3.…”
Section: Accepted Manuscript 13mentioning
confidence: 65%
“…It is reported that GPX3 is related to many malignancies including including head and neck, ovarian, and colon tumors (29,30). Hypermethylation of the GPX3 promoter reduces GPX3 expression (31,32). Furthermore, decreased GPX3 expression could inhibit clonogenicity and anchorageindependent cell survival in ovarian cancer progression (33).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing or decreased activity of GPX3 is correlated with increased ROS level and contributes to cancer initiation [51] and metastasis [52,53]. Reduced expression of GPx3 could enhance platin sensitivity in colorectal cancer [54], and increased expression was related with low intracellular ROS level and maintaining cancer stem cell phenotype in leukemia stem cells [36]. Two intronic polymorphisms of GPx3, rs3805435 and rs3828599, were shown to influence gene expression and correlate with gastric cancer risk [55].…”
Section: Discussionmentioning
confidence: 99%